REVIVAL OF ANCIENT GREEK TRAGEDY CONCEPTS IN THE TRAGEDY BY J. O’NEILL “MOURNING – DESTINY OF ELECTRA” - Derbenyova , L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the original adaptation by Engine O’Neill of the stheme of Oresteia to the aftermath of the American Civil War in his trilogy Morning Becomes Electra. It examines perpetual ontologic problems through the prism of myth in connection with recent expliant interest of literary crities in myth criticism, mythologic and mythopoetic.